2014
DOI: 10.1097/wnr.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Fiction feelings in Harry Potter

Abstract: Immersion in reading, described as a feeling of 'getting lost in a book', is a ubiquitous phenomenon widely appreciated by readers. However, it has been largely ignored in cognitive neuroscience. According to the fiction feeling hypothesis, narratives with emotional contents invite readers more to be empathic with the protagonists and thus engage the affective empathy network of the brain, the anterior insula and mid-cingulate cortex, than do stories with neutral contents. To test the hypothesis, we presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 19 publications
2
59
1
Order By: Relevance
“…The MCC is particularly interesting in the context of mindfulness meditation as it has been conceptualized as integrating emotionally salient interoceptive information that may ultimately result in improved movement–balance activity [56]. One study showed that the MCC was activated when subjects read emotionally evocative (versus neutral) stories and that its activation was correlated with self-reported feelings of “immersion” while reading [57]. Yet, other studies have shown the MCC’s involvement in environmental monitoring, response selection, and motor body orientation [58].…”
Section: Discussionmentioning
confidence: 99%
“…The MCC is particularly interesting in the context of mindfulness meditation as it has been conceptualized as integrating emotionally salient interoceptive information that may ultimately result in improved movement–balance activity [56]. One study showed that the MCC was activated when subjects read emotionally evocative (versus neutral) stories and that its activation was correlated with self-reported feelings of “immersion” while reading [57]. Yet, other studies have shown the MCC’s involvement in environmental monitoring, response selection, and motor body orientation [58].…”
Section: Discussionmentioning
confidence: 99%
“…So far, immersion appears the only process that has been examined with neurocognitive methods. For example, in an fMRI study on immersive experiences taking place while reading emotion-laden versus neutral passages of Harry Potter, the emotion-laden passages resulted in stronger correlations between blood oxygenation level dependent (BOLD) signals in neural substrates associated with empathy on the one hand and post hoc immersion ratings on the other (Hsu et al, 2014). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Other metaphors than Balázs’ are popular in the literature, e.g., absorption or transportation, but at present both the conceptual work and empirical data base is not enough developed to allow sharp distinctions (Jacobs and Schrott, 2015; Jacobs and Lüdtke, in press). What seems clear is that young and adult readers long for immersion into novels like Harry Potter and a few pioneering studies have begun to investigate the neurocognitive and –affective underpinnings of this phenomenon (Hsu et al, 2014; Lüdtke et al, 2014). It is less clear whether readers’ longing for poetry like Shakespeare’s or Pushkin’s, as well as highly foregrounded narratives from Joyce or Proust is based on the same kind of neuropsychological processes or linked more to processes of aesthetic appreciation, as proposed by the Neurocognitive Poetics Model (NCPM; Jacobs, 2011, 2015a, 2016b; cf.…”
Section: Liking Words and Ludic Readingmentioning
confidence: 99%
“…Good “storytelling, inevitably, is about compelling human plights that are “accessible” to readers.” (Bruner, 1986, p. 35), i.e., make the comprehension of the plans underlying the goal-directed actions of its protagonists easy by facilitating situation model building and mental simulation through theory of mind processes of empathy and identification which all facilitate immersion (e.g., Mason and Just, 2009; Mar, 2011; Altmann et al, 2012, 2014; Hsu et al, 2014; Jacobs and Lüdtke, in press). According to Brewer and Lichtenstein (1982) stories differ from narratives in that they are structured to evoke a particular affective response pattern in the readers.…”
Section: Multiword Expressionsmentioning
confidence: 99%